Short-Term and Long-Term FK506 Treatment Alters the Vascular Reactivity of Renal and Mesenteric Vascular Beds - Guray Soydan; Ender Tekes; Meral Tuncer (Elsevier, 2006)
The aims of this study were to investigate the role of endothelin-1 in FK506-induced hypertension and vascular dysfunction of rats treated with the drug for 8 (short-term) or 30 (long-term) days and to measure malondialdehyde levels in the kidneys. Kidney and mesentery of rats were perfused. In the short-term treated groups, there was no significant change in systolic blood pressure. The response to noradrenaline only in renal vascular beds was significantly increased by FK506 and this increase was prevented by Bosentan. FK506 had no significant effect on sodium nitroprusside-induced vasodilation in comparison with solvent in both vascular beds. Bosentan failed to prevent these responses. In the long-term treated groups, at the end of the treatment with FK506, there was a significant increase in blood pressure, but no change in the response to noradrenaline in either kidneys or mesentery. The increase in blood pressure was prevented by bosentan treatment. FK506 increased malondialdehyde levels in the kidneys of the rats from only the long-term treated groups. Bosentan did not change this increase. Our results indicated that endothelin-1 plays a key role in the FK506-induced change in vascular reactivity to noradrenaline in renal vascular beds and drug-induced hypertension in the rats. There was no relationship between oxidative stress and FK506-induced hypertension. Keywords:: bosentan, endothelin-1, isolated perfused kidney and mesentery, malondialdehyde, tacrolimus (FK506)